The Impact of Union Presence and Strategic Human Resource Management on Employee Voice in Multinational Enterprises in Australia - Sablok, Gitika; Bartram, Timothy; Stanton, Pauline; Burgess, John; McDonnell, Anthony (Sage Journals, 2013)
In this article, we examine the use and character of employee voice mechanisms of foreign-owned multinational enterprises operating in Australia, as well as the influence of a strategic human resource management approach and union presence. Findings indicate that foreign-owned multinational enterprises are high-level users of the full range of employee voice mechanisms, with the exceptions of use of employee suggestion schemes, trade union recognition and the use of joint consultation committees across all sites. Using logistic regression analysis, findings show that trade union presence, a strategic human resource management approach, greenfield site and country of origin impact the employee voice approach adopted. High trade union presence is associated with an indirect employee voice approach. A low trade union presence is associated with a direct or a minimalist approach to employee voice. Moreover, a strategic human resource management approach is associated with both direct and dualistic approaches to employee voice. Implications are drawn for theory and practice.